2001
DOI: 10.1021/bi0112715
|View full text |Cite
|
Sign up to set email alerts
|

Copper Trafficking:  the Solution Structure of Bacillus subtilis CopZ

Abstract: A sequence with a high homology (39% residue identity) with that of the copper-transport CopZ protein from Enterococcus hirae and with the same MXCXXC metal-binding motif has been identified in the genome of Bacillus subtilis, and the corresponding protein has been expressed. The protein, constituted by 73 amino acids, does bind copper(I) under reducing conditions and fully folded in both copper-bound and copper-free forms under the present experimental conditions. The solution structure of the copper-bound fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
148
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(166 citation statements)
references
References 40 publications
17
148
1
Order By: Relevance
“…MBDs are 60-to 70-aa-long domains. They have a ␤␣␤␤␣␤ fold and an invariant CXXC metal-binding sequence similar to the well described Cu ϩ chaperones, Atox1, Atx1, and CopZ (20,22,23). N-MBDs bind Cu ϩ with high affinity (24)(25)(26), and in vivo, they receive Cu ϩ from the corresponding Cu ϩ chaperones (23,27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MBDs are 60-to 70-aa-long domains. They have a ␤␣␤␤␣␤ fold and an invariant CXXC metal-binding sequence similar to the well described Cu ϩ chaperones, Atox1, Atx1, and CopZ (20,22,23). N-MBDs bind Cu ϩ with high affinity (24)(25)(26), and in vivo, they receive Cu ϩ from the corresponding Cu ϩ chaperones (23,27,28).…”
mentioning
confidence: 99%
“…However, Cu ϩ does not access the ATPase as a free (hydrated) ion but is bound to a chaperone protein. Cu ϩ chaperones that deliver metal specifically to Cu ϩ -ATPases have been identified in a range of organisms (4,20,22). We recently described the A. fulgidus Cu ϩ chaperone CopZ (32).…”
mentioning
confidence: 99%
“…1A). Structural work has demonstrated that Cu chaperones and target metal-binding domains from various organisms possess the same fold and coordinate the metal via two surfaceexposed cysteines in the MXCXXC motif (13)(14)(15)(16)(17)(18)(19)(20)(21). Although the methionine in the first position of the MXCXXC motif is conserved in all organisms, it is not directly involved in metal ligation (13).…”
mentioning
confidence: 99%
“…The Atox1 metallochaperone and its homologs, both eukaryotic and prokaryotic, contain a single CXXC motif (14). Crystal and solution structures of Atox1 (15), yeast Atx1 (16,17), bacterial CopZ (18,19), and single domains of MNK (20) and Ccc2 (21) reveal a conserved ␤␣␤␤␣␤-fold with the cysteines from the CXXC motif coordinating metal ions on a surface-exposed loop. Notably, the CXXC motifs from two Atox1 molecules coordinate a single Cu(I) ion in the x-ray structure (15).…”
mentioning
confidence: 99%